A multiplex microsatellite set for non-invasive genotyping and sexing of the osprey (Pandion haliaetus) - Dawson, Deborah A. (Conserv Genet Resour, 2015)
During the 1950s and 1970s the osprey (Pandion haliaetus) experienced a dramatic population crash and remains of conservation concern in several parts of the world. We isolated 37 microsatellite loci and assessed these in ospreys sampled in the UK and Norway (using mouth swabs/feathers). From 26 loci variable in four ospreys, we selected 13, combined these into two multiplex-PCR sets and included a sex-typing marker. Additional markers confirmed sexes. In 17 ospreys, feather-sampled in central Norway, we found 3–10 alleles per locus. The 13 loci are autosomal (heterozygotes were present in both sexes) and observed heterozygosities ranged from 0.24 to 0.94. The combined probability of identity for the 13 loci was 8.0 × 10(−12). These microsatellite loci will be useful for genetic monitoring, parentage analysis and population genetic studies of the osprey. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12686-015-0497-4) contains supplementary material, which is available to authorized users.